OVERVIEW OF SMALL BUSINESS IN RURAL AREAS OF AFGHANISTAN - Dr. Khujamurodov Askarjon Jalolovich; Mamadjanova Tuygunoy Ahmadjanovna; Sayed Hujatullah Ahmadi Ibn Sayed Ahmadullah (Galaxy International Interdisciplinary Research Journal, 2021)
In this article and scientific research, an attempt has been made to study the various dimensions of small businesses in rural areas of Afghanistan, including the general introduction of small businesses in Afghanistan and the rural population, national programs supported small businesses over the past two decades which Implemented or ongoing, the inclusion of small business development program in the Afghan National Development Strategy, definition of rural enterprises from the perspective of the Afghan Ministry of Rural Development, Examples of different types of small businesses in addition to agriculture and livestock which are the main sources of income for rural people, major challenges for the development of small businesses in rural Afghanistan, recommendations for the future of rural small businesses to play a major role in Afghanistan’s economic growth And poverty reduction in rural communities and at the conclusion trying to analysis the situation of small businesses in rural areas of Afghanistan.